Diffusion imaging of fornix and interconnected limbic deep grey matter is linked to cognitive impairment in multiple sclerosis. (2nd December 2021) - Valdés Cabrera, Diana; Smyth, Penelope; Blevins, Gregg; Emery, Derek; Beaulieu, Christian
Abstract: Diffusion tensor imaging (DTI) and volumetric magnetic resonance imaging (MRI) have shown white matter (WM) and deep grey matter (GM) abnormalities in the limbic system of multiple sclerosis (MS) participants. Structures like the fornix have been associated with cognitive impairment (CI) in MS, but the diffusion metrics are often biased by partial volume effects from cerebrospinal fluid (CSF) due to its small bundle size and intraventricular location. These errors in DTI parameter estimation worsen with atrophy in MS. The goal here was to evaluate DTI parameters and volumes of the fornix, as well as associated deep GM structures like the thalamus and hippocampus, with high‐resolution fluid‐attenuated inversion recovery (FLAIR)‐DTI at 3T in 43 MS patients, with and without CI, versus 43 controls. The fornix, thalamus and hippocampus displayed atrophy and/or abnormal diffusion metrics, with the fornix showing the most extensive changes within the structures studied here, mainly in CI MS. The affected fornix volumes and diffusion metrics were associated with thalamic atrophy and atypical diffusion metrics in interconnected limbic GM, larger total lesion volume and global brain atrophy. Lower fractional anisotropy (FA) and higher mean and radial diffusivity in the fornix, lower hippocampus FA and lower thalamus volume were strongly correlated with CI in MS. Hippocampus FA and thalamus atrophy were negatively correlated with fatigue and longer time since MS symptoms onset, respectively. FLAIR‐DTI and volumetric analyses provided methodologically superior evidence for microstructural abnormalities and extensive atrophy of the fornix and interconnected deep GM in MS that were associated with cognitive deficits. Abstract : Limbic structures, such as the fornix, play important roles in memory. The diffusion metrics and volumes of the fornix and its interconnecting deep grey matter were found abnormal when evaluating cognitive impairment in multiple sclerosis (MS) with cerebrospinal fluid‐suppressed diffusion tensor imaging. Findings here provided evidence of fornix microstructural and volume abnormalities and thalamic atrophy in MS, which might be a prospective diagnostic marker of cognitive deficits.